Ds Marié Joseph Goddefroy as volksman - Botha, Schalk Jacobus (Hervormde teologiese studies, 1987)
The Rev MJ Goddefroy as an Afrikaner patriot To honour prof AD Pont, a devoted Afrikaner patriot himself, on his sixtieth birthday (21 September), this paper pays attention to the patriotism of the Rev Goddefroy who, one hundred years ago in 1887, came from the Netherlands to the Zuid-Afrikaansche Republiek. Here he not only became a minister of the Nederduitsch Hervormde Kerk, but he also heartily adopted the Afrikaner as his own people and made their ideals his own.